2005
DOI: 10.1017/s0963180106060117
|View full text |Cite
|
Sign up to set email alerts
|

Dissatisfaction with Ethics Consultations: The Anna Karenina Principle

Abstract: We gratefully acknowledge the contributions of Jeffrey Blustein, Kathleen B. Briggs, Ronald Cranford, Glen I. Komatsu, and Ernle W.D. Young to the original randomized controlled trial phase of this research. Grant support came from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 1 publication
0
17
0
2
Order By: Relevance
“…Many of these studies reported findings on physician satisfaction [11,12,15,16], and physician’s perception of clarifying ethical issues, educating the health care team, making clinical decisions with confidence, and in patient management [18]. However, the satisfaction or perception of the parties involved may be influenced by factors not associated with the quality of the HCEC conducted [17,22]. For example, a physician may be satisfied with the HCEC service provided because his/her suggestion is adopted by the ethics consultant and not because of the quality of the HCEC service.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies reported findings on physician satisfaction [11,12,15,16], and physician’s perception of clarifying ethical issues, educating the health care team, making clinical decisions with confidence, and in patient management [18]. However, the satisfaction or perception of the parties involved may be influenced by factors not associated with the quality of the HCEC conducted [17,22]. For example, a physician may be satisfied with the HCEC service provided because his/her suggestion is adopted by the ethics consultant and not because of the quality of the HCEC service.…”
Section: Discussionmentioning
confidence: 99%
“…Appraisals by external CEC members not involved in the particular CECons [76,99,108,128,129] iii. Feedback from patients and family members [14,69,74,91,92,114,130,131] iv. Input from healthcare professionals [5,14,15,33,72,74,80,85,87,90,91,98,103,111,112,114,118,119,127,130] v. Evaluations by senior clinicians [82,84,93,102,104,127] vi.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Several studies examine stakeholder satisfaction, which is generally found to be high–with health professionals giving the highest scores and next of kin and patients somewhat lower, but still mainly positive 3 4. In Schneiderman et al ’s multicentre study from an intensive care unit setting, ethics consultation received a positive evaluation by more than 90% of health professionals and 80% of patient surrogates 5…”
Section: Introductionmentioning
confidence: 99%